2019
DOI: 10.17886/rki-gbe-2018-100
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of early detection examinations by children in Germany. Results of the cross-sectional KiGGS Wave 2 study

Abstract: Examinations for early detection of diseases (called U-Untersuchungen in Germany) are among the most important prevention measures at childhood age. According to KiGGS Wave 2 data, participation rates are over 95% for most of these examinations. 99.7% and 99.6% of children, respectively, who had reached the recommended age for these examinations participated in the U1 and U2 examinations, 98.0% and 98.1%, respectively, the U8 and U9 examinations. Participation rates for children from families with low socioeco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The fifth check-up (U5), which has to be undertaken between the sixth and seventh month of life, includes the explicit check for undescended testis [26]. As almost all of the children in Germany participate in the U5 [27], primary undescended testis should be detected up to the seventh months of life. Despite this early check-up numbers of procedures for orchidopexy, cryptorchism and abdominal testis were 10% in 2010 and went up to 12% in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…The fifth check-up (U5), which has to be undertaken between the sixth and seventh month of life, includes the explicit check for undescended testis [26]. As almost all of the children in Germany participate in the U5 [27], primary undescended testis should be detected up to the seventh months of life. Despite this early check-up numbers of procedures for orchidopexy, cryptorchism and abdominal testis were 10% in 2010 and went up to 12% in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…These results are unexpected; as several studies in the field of early detection and prevention have demonstrated that, inter alia, education and income, as well as the composite index of socio-economic status, have an influence on participation. For example, the baseline survey and the two follow-up surveys of the Study on the Health of Children and Adolescents in Germany (KiGGS) showed that children with a lower socio-economic status are significantly less likely to use preventive check-ups compared to children with a medium or high socio-economic status [ 12 , 25 , 30 ]. Most regional studies examining the relationship between uptake of preventive or screening examinations and education of the parents have also achieved the similar result [ 7 , 14 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…U1-U9, J1) offered by the statutory health insurance. It has also been found that adolescents with a migration background participate in the early detection examination J1 (between 12 and 14 years) only half as often as adolescents without a migration background [ 6 , 7 , 25 , 30 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous analyses of these early diagnosis examinations have mainly focused on participation rates and behaviour. Here, a social gradient is partly evident [ 11 15 ]. For this reason, it will also be investigated whether the generated results apply to all subgroups irrespective of education and income among other things.…”
Section: Introductionmentioning
confidence: 99%